Peran G20 dalam Pemulihan Ekonomi Global Pasca Covid-19 - Rahmadan, Yanuar; Sabrina, Rorina (Department of Political Science - Universitas Sains Al-Qur’an, 2024)
Covid-19 pandemic has caused countries to experience economic downturn, especially countries that are categorized as vulnerable and fragile. The G20, as one of the intergovernmental forums, was encouraged by the International Monetary Fund and World Bank to take part in the economic recovery effort. The Debt Service Suspension Initiative program (DSSI) is taken, aimed at countries that are categorized as vulnerable and fragile. DSSI is aimed to provide debt relief to ease financial burden from the countries during the Covid-19 pandemic. This research uses a qualitative research method, exploring the issue through literature review. Angola, Pakistan and Somalia as the three countries that received the largest debt suspension based on World Bank data are used as the sample. The international regime theory is also used to analyze the role of G20 in providing debt service suspension. The result from the study is that the debt service suspension has positively impact Angola and Somalia. G20, as an international regime has also followed the principles it recognizes since its establishment and has set of rules and procedures related to the debt suspension initiative through the G20 Action Plan. In addition, G20 also acknowledges the existence of global macroeconomic interdependence, hence G20 established DSSI for countries in the vulnerable and fragile categories.